EFFORTS TO INCREASE EARLY CHILDREN'S INTEREST IN LEARNING THROUGH GRAIN MATERIAL COLLAGE MEDIA IN GROUP B AT KINDERGARTEN SEJAHTERA II NAMORAMBE : EFFORTS TO INCREASE EARLY CHILDREN'S INTEREST IN LEARNING THROUGH GRAIN MATERIAL COLLAGE MEDIA IN GROUP B AT KINDERGARTEN SEJAHTERA II NAMORAMBE - Krismayana Sembiring; Aminda Tri Handayani (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
Interest in learning is important to grow and develop in children so that children are interested and motivated in learning. The collage technique is one of the activities to increase children's interest in learning. This research aims to increase children's desire to learn through teaching using collage techniques with grain material for children aged 5-6 years. This research was conducted at Sejathtera II Namorambe Kindergarten, Namorambe District, Deli Serdang Regency, with research subjects 14 group B children aged 5-6 years. This research uses classroom treatment consisting of 2 cycles, where one cycle consists of 4 components, which include planning, action, observation and reflection. Data analysis uses the Classroom Action Research (PTK) method. The results of the research showed that in initial conditions there was only 20% of the class average, and action was taken in cycle 1 resulting in an increase of 58% in children's interest in learning. The increase that occurred has not met the target, so treatment needs to be carried out in cycle II. As a result, children's interest in learning increased to 87% after taking action in cycle II. In this way, the collage technique made from grain materials can increase interest in learning among group B students at Sejathtera II Namorambe Kindergarten, Namorambe District, Deli Serdang Regency.